The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s0080-62342011000700008
|View full text |Cite
|
Sign up to set email alerts
|

Fluência digital e uso de ambientes virtuais: caracterização de alunos de enfermagem

Abstract: RESUMO RESUMENEste estudio objetivó caracterizar el perfil de alumnos de enfermería, identificar su fluidez digital, conocimiento, habilidad e interés en uso de ambientes virtuales de aprendizaje. Investigación cuantitativa, exploratorio-descriptiva, realizada con 51 alumnos de Enfermería mediante cuestionario. De los participantes, 51 (100%) afirman tener conocimientos de informá-tica, 26 (49%) refieren nivel intermedio; 47 (92%) utilizan Internet diariamente; 51 (100%) participan en redes sociales y poseen e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
0
25

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 13 publications
(14 reference statements)
2
1
0
25
Order By: Relevance
“…It is up to the educational institutions to identify the needs and preferences of their students to incorporate new learning methods. 30,31 In the present study, the results of the usability evaluation with the target audience demonstrated a high level of satisfaction with SEMIOVAPE, similarly to what was found in a previous study, in which students agreed with the ease of navigating the object. 30 In this sense, the VLO is characterized as a pleasant study environment, being a complementary tool to the classes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is up to the educational institutions to identify the needs and preferences of their students to incorporate new learning methods. 30,31 In the present study, the results of the usability evaluation with the target audience demonstrated a high level of satisfaction with SEMIOVAPE, similarly to what was found in a previous study, in which students agreed with the ease of navigating the object. 30 In this sense, the VLO is characterized as a pleasant study environment, being a complementary tool to the classes.…”
Section: Discussionsupporting
confidence: 89%
“…30,31 In the present study, the results of the usability evaluation with the target audience demonstrated a high level of satisfaction with SEMIOVAPE, similarly to what was found in a previous study, in which students agreed with the ease of navigating the object. 30 In this sense, the VLO is characterized as a pleasant study environment, being a complementary tool to the classes. 32 The interest in learning the most varied contents, using this technology, as reported by the participants, reinforces this understanding.…”
Section: Discussionsupporting
confidence: 89%
“…22 Por outro lado, ressalta-se que o sucesso do aluno virtual está diretamente ligado à ferramenta utilizada, à forma pela qual o professor conduz sua turma e, principalmente, pela motivação para realizar as atividades on-line e disponibilidade de recursos necessários para a interatividade desejada. 23 É constatado que quando há união do método presencial com o ensino on-line, por meio da interação de atividades virtuais e de aulas teóricas presenciais, revela-se uma estratégia muito mais eficiente para alcance dos objetivos educacionais. Portanto, o uso de hipermídia pode ser considerado uma ferramenta digital complementar ao ensino presencial, o que facilita a aprendizagem dos discentes.…”
Section: Discussionunclassified
“…Os recursos disponibilizados pelas TICs, em especial os ambientes virtuais de aprendizagem favorecem o processo de construção do conhecimento e interação entre alunos, professores, tutores e profissionais, enriquecendo o compartilhamento de ideias e possibilitando uma aprendizagem dinâmica e colaborativa. (COSTA et al, 2011).…”
Section: Acredito Que O Projeto Ajudará Muito Pois As Informações Neunclassified